2021
DOI: 10.1007/s10750-021-04752-1
|View full text |Cite
|
Sign up to set email alerts
|

Carbon fluxes in subtropical shallow lakes: contrasting regimes differ in CH4 emissions

Abstract: Article 25fa pilot End User AgreementThis publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the work.This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…In contrast, lower values were reported for an Amazon floodplain, including areas of OW, colonized by floating macrophytes and of flooded forest, although there were no differences in CH 4 diffusive flux between habitats (0.04–0.97 mmol m −2 d −1 , Barbosa et al 2020). Lower values were also reported for a shallow boreal lake, including areas of OW, submerged and emergent vegetation (0.24–1.1 mmol m −2 d −1 , Desrosiers et al 2022), yet much higher values were reported for littoral and pelagic areas of clear and turbid shallow lakes of Uruguay (61.3–270.7 mmol m −2 d −1 , Colina et al 2021). CH 4 ebullitive flux ranged from 0.27 mmol m −2 d −1 in winter up to 27.7 mmol m −2 d −1 in summer, with an annual mean of 4.7 ± 7.5 mmol m −2 d −1 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, lower values were reported for an Amazon floodplain, including areas of OW, colonized by floating macrophytes and of flooded forest, although there were no differences in CH 4 diffusive flux between habitats (0.04–0.97 mmol m −2 d −1 , Barbosa et al 2020). Lower values were also reported for a shallow boreal lake, including areas of OW, submerged and emergent vegetation (0.24–1.1 mmol m −2 d −1 , Desrosiers et al 2022), yet much higher values were reported for littoral and pelagic areas of clear and turbid shallow lakes of Uruguay (61.3–270.7 mmol m −2 d −1 , Colina et al 2021). CH 4 ebullitive flux ranged from 0.27 mmol m −2 d −1 in winter up to 27.7 mmol m −2 d −1 in summer, with an annual mean of 4.7 ± 7.5 mmol m −2 d −1 .…”
Section: Discussionmentioning
confidence: 92%
“…CH 4 ebullitive flux ranged from 0.27 mmol m −2 d −1 in winter up to 27.7 mmol m −2 d −1 in summer, with an annual mean of 4.7 ± 7.5 mmol m −2 d −1 . A similar annual mean was found for boreal ponds (4.6 ± 4.1 mmol m −2 d −1 , DelSontro et al 2016), for an Australian subtropical wetland (5.5 ± 9.7 mmol m −2 d −1 ; Jeffrey et al 2019 a ), for the littoral zone of a clear shallow lake and for the pelagic zone of a turbid shallow lake from Uruguay (5.0 ± 0.2 and 3.6 ± 0.2 mmol m −2 d −1 , respectively; Colina et al 2021). Yet, a lower mean was reported for a set of Brazilian water bodies (1.1 ± 2.4 mmol m −2 d −1 ; Oliveira Junior et al 2021), for an Amazon floodplain (1.1 ± 2.6 mmol m −2 d −1 ; Barbosa et al 2020) and for the unvegetated littoral of a shallow boreal lake (1.84 ± 2.6 mmol m −2 d −1 , Desrosiers et al 2022), although Desrosiers et al (2022) also reported higher means in the areas colonized by the emergent macrophyte Typha latifolia and submerged macrophyte Brasenia schreberi (6.81 ± 10.8 and 15.9 ± 18.9 mmol m −2 d −1 , respectively).…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies of carbon dioxide (CO 2 ) and methane (CH 4 ) fluxes in shallow lakes, showing strong variation depending on the dominant primary producers, but subtropical systems are understudied. Colina et al ( 2022 ) compared summer CO 2 and CH 4 fluxes (diffusion and ebullition) in littoral and pelagic zones of three subtropical shallow lakes with contrasting states (clear to turbid). Significant differences among the lakes only occurred for CH 4 fluxes.…”
Section: The Volumementioning
confidence: 99%
“…Urban lakes (normally with a mean depth of less than 3 m) are commonly shallow [12,13] and are indispensable components of landscape features and urban living environments [14,15]. Urban lakes have a vulnerability to a host of anthropogenic and environmental pressures and possess a poor capacity for self-purification [16]. Human activities, for instance, discharges of wastewater, can enhance loadings of organic carbon and nutrients in urban lakes, which can stimulate mineralization and thus promote methanogenesis [17].…”
Section: Introductionmentioning
confidence: 99%